Link of Nasopharyngeal Carcinoma and Epstein-Barr Virus - Sugiyanto Sugiyanto; Lina Aryati; Fajar Adi Kusumo; Mardiah Suci Hardianti (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2018)
Nasopharyngeal Carcinoma (NPC) is a cancer that occurs in nasopharynx which is associated with Epstein-Barr Virus (EBV). Mutation agents in nasopharyngeal neoplasms occur because of EBV infection. Transformation of B-cells due to EBV causes hormone imbalance in lymphoid cells or nasopharyngeal epithelial tissue. Rates of EBV infection have been shown to be prognostic to NPC. The basic level of EBV DNA can be used for stratification prognosis, with higher titers showing greater disease severity and worse outcomes. With mathematical models, there is a correlation between the increase in Epstein-Barr Virus and the increase in Invasive Carcinoma Cells or increase in Nasopharyngeal Carcinoma Cells.